1996
DOI: 10.1136/ard.55.5.317
|View full text |Cite
|
Sign up to set email alerts
|

Association of two loci on chromosome 2q with nodal osteoarthritis.

Abstract: Objective-To search for genetic association between microsatellite marker loci and sibling pairs with nodal osteoarthritis (NOA).Methods-Using the affected sibling pair method ofanalysis, genomic DNA from 66 sib pairs with NOA was analysed for association with highly polymorphic microsatellite marker loci. The microsatellite markers were amplified using polymerase chain reaction and typed on polyacrylamide gels. Results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 10 publications
0
33
0
1
Order By: Relevance
“…Several groups of investigators have performed genome-wide screens of sibling pairs or nuclear families with OA and reported multiple chromosome areas (e.g., 2q13-14, 2q24-32, 2p24, 3p12, 4q32, 11q12, 9q33-34, 4q27, Xp11.3, and 7p22) that show positive linkage to specific OA phenotypes, such as radiographic OA (ROA) in the distal interphalangeal (DIP) joints, severe end-stage disease (based on hip replacement surgery), and nodal OA (7)(8)(9)(10)(11)(12)(13). When investigating end-stage disease (joint replacement surgery) (8), nodal OA (7), or DIP joint OA (11), the most consistent linkage was reported for a broad region on human chromosome 2q13-32.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups of investigators have performed genome-wide screens of sibling pairs or nuclear families with OA and reported multiple chromosome areas (e.g., 2q13-14, 2q24-32, 2p24, 3p12, 4q32, 11q12, 9q33-34, 4q27, Xp11.3, and 7p22) that show positive linkage to specific OA phenotypes, such as radiographic OA (ROA) in the distal interphalangeal (DIP) joints, severe end-stage disease (based on hip replacement surgery), and nodal OA (7)(8)(9)(10)(11)(12)(13). When investigating end-stage disease (joint replacement surgery) (8), nodal OA (7), or DIP joint OA (11), the most consistent linkage was reported for a broad region on human chromosome 2q13-32.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent genomewide searches were performed previously, of nodal OA 21 and hip replacement 22 that showed linkage to chromosome 2q32 encompassing the locus identified in our initial analyses. Two functional variants within the FRZB gene was subsequently found that explained the linkage and were associated to hip replacement in females, 6 signifying the Wnt signaling pathway in the pathogenesis of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Upon fine mapping analysis, our locus shifted from the 2q32 toward the telomere, thereby discarding the overlap with the previously observed linkage in this region. 21,22 Two promising candidate genes for the FOA phenotype, PTHR2 and the FZD5, mapped within the minimal cosegregating haplotype. The FZD5 gene encodes the Wnt signaling receptor FZ5 for the Wnt5A ligand 23 and might agonist FRZB.…”
Section: Discussionmentioning
confidence: 99%
“…A number of linkage studies of OA at different sites have been performed in single large pedigrees and in multiple families (6)(7)(8)(9)(10)(11)(12)(13)(14). The genes responsible for the observed linkage peaks have not yet been clearly determined or validated, and results from different linkage studies show little overlap.…”
mentioning
confidence: 99%